2011
DOI: 10.1089/ars.2010.3275
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Human Health and Disease

Abstract: This review covers current knowledge of selenium in the environment, dietary intakes, metabolism and status, functions in the body, thyroid hormone metabolism, antioxidant defense systems and oxidative metabolism, and the immune system. Selenium toxicity and links between deficiency and Keshan disease and Kashin-Beck disease are described. The relationships between selenium intake/status and various health outcomes, in particular gastrointestinal and prostate cancer, cardiovascular disease, diabetes, and male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
820
1
34

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,091 publications
(910 citation statements)
references
References 378 publications
(406 reference statements)
14
820
1
34
Order By: Relevance
“…It is found within the body mainly as selenomethionine or as selenocystein in various selenoproteins. Of those, glutathione peroxidase (GPx) , thioredoxin reductase and selenoprotein P are some of the most important [14].…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found within the body mainly as selenomethionine or as selenocystein in various selenoproteins. Of those, glutathione peroxidase (GPx) , thioredoxin reductase and selenoprotein P are some of the most important [14].…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
“…[33] Intake of selenium The dietary intake of selenium differs throughout the world, In Europe the estimated mean intake of selenium is 40 μg/day [34] , whereas the mean intake in the US is estimated to be 134 μg/day in men and 93 μg/day in women [35]. The differences can mainly be explained by the poor selenium content of the soil in Europe, compared to the US, or the Australian soils [14]. In the French EVA (Etude du Vieillissement Artériel) study where an elderly population was evaluated, it was demonstrated an association between low plasma concentration of selenium and mortality [36].…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
“…Selenium (Se) has antioxidant properties so that it is necessary for humans and animals (Fairweather-Tait et al, 2011). Selenium is trace elements needed by the animal and human (Chaudhary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The redox-protective properties of selenium are important during oxidative thyroid hormone production, in which thyroid cells produce excess H 2 O 2 and reactive oxygen species. Due to its ability to protect the thyroid gland and maintain thyroid hormone production, there is a high concentration of selenium in the thyroid (Aaseth et al, 1990), and supply of selenium to the thyroid is prioritized even during periods of selenium deficiency (Fairweather-Tait et al, 2011).…”
Section: Introductionmentioning
confidence: 99%